Encyclopedia of white-collar & corporate crime - Salinger, Lawrence M. (Gale virtual reference library, 2005)
Covers the history of white-collar and corporate crime. Serves as a general and non-technical resource for criminology and history students, librarians, and professors to understand the development of white-collar and corporate crime in the U. S. as well as internationally; to appreciate the business forces that can affect daily life; and to initiate educational discussion brought forth by the specific historical and topical articles presented in the work.